Comparative Finite Element Analysis of Wear Repair Methods for Vertical Kaplan Turbine Shafts Based on Structural and Dynamic Responses - Marudut Tarihoran; Achmad Syaifudin (Universitas Panca Marga, 2026)
Non-uniform journal wear on the vertical Kaplan turbine shaft increases shaft–bearing clearance, resulting in higher vibration and reduced operational reliability. This study evaluates the structural and dynamic effects of shaft wear and compares two restoration methods: Belzona 1111 coating and an SS410 stainless-steel shock sleeve. Finite Element Analysis (FEA) was performed in ANSYS Workbench using static structural and modal analyses for four shaft conditions: intact, worn, Belzona-restored, and shock sleeve-repaired. The numerical model was validated against the theoretical critical speed, yielding an error of 8.32%. The worn shaft exhibited the highest radial deformation (0.033123 mm), indicating a significant reduction in structural stiffness. Belzona restoration reduced deformation by 36.23%, while the SS410 shock sleeve achieved a 97.68% reduction, restoring shaft deformation close to the intact condition (0.00076983 mm). Although natural frequencies showed only minor variations among all cases, the shock sleeve produced the smallest deviation from the intact shaft and the most symmetrical mode shapes, indicating superior dynamic performance. The results demonstrate that journal wear primarily degrades shaft stiffness rather than natural frequencies. Among the evaluated restoration methods, machining followed by installation of an SS410 shock sleeve provides the closest structural and dynamic characteristics to the original shaft, making it the most effective solution for improving the reliability and operational stability of vertical Kaplan turbine shafts.